The effects of pre-writing activities on the 12th graders’ learning of paragraph writing - An action research project at Yen Lac High School, Vinh Phuc - Nguyễn, Thị Nhung (2020)
This study aims at examining the effects of pre-writing activities on the 12th graders‟ learning of paragraph writing. To reach this aim, an action research was conducted with forty-five 12th grade students at Yen Lac High School in the second semester of the year 2015-2016. They were chosen from the same class to take part in pre-writing activities in writing lessons for eight weeks. The data were gathered through qualitative and quantitative data. The qualitative data were obtained from analyzing the class observation result and quantitative data were gained by students' pretest, posttest and questionnaires for students. The result of this research indicated that there was an improvement in students' writing performance. Moreover, from the result of questionnaires, it also showed that there was improvement of positive response in teaching-learning process of writing with pre-writing activities. Besides, the result of observation showed that students were interested in the teachinglearning activities during the implementation of pre-writing activities. The findings, suggestion, suitable and effective ways for teachers in applying pre-writing activities in class to make certain positive changes in their teaching methodology as well as to help students improve their writing performance